PLANTAIN PRICES IN DOUALA - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
What is the market price for a banana bunch (30-40 kg) in Douala (Cameroon)?That depends upon the time of year. The volatility of banana prices can mainly be explained by seasonal variations in supply, which in turn are dictated by plantation,...